The Role of Islamic Education Teachers in The Development of Religious Culture - Khoirun Nisa’; Lum'atul Af'idah (SCHOOLAR: Social and Literature Study in Education, 2021)
The teacher is one of the factors that influence the process of growth and development of the student's personality. One form of personality that must be instilled in students is a religious person. An Islamic teacher not only teaches Islamic religious education, but also makes other efforts that can help achieve the goals of Islamic religious education. These efforts are realized through the role of Islamic religious teachers in realizing religious culture in schools. Religious culture in schools is a way of thinking and acting for school residents based on religious values. This has been realized and entrenched in Madrasah Muallimin Muallimat Tambakberas Jombang since the beginning of the establishment of this Educational Institution because it integrates with existing education in Pondok Pesantren which is based on religious values.